Unravelling the potential of rice congee: A review of its physicochemical properties, processing methods, functional food opportunities, and current hurdles - Shaharom, Noor Farisya Mohd; Seow, Lay-Jing; Yusoff, Anida; Seow, Eng-Keng (Journal of Food Technology Research, 2023)
The purpose of the article is to go through how to make porridge and congee, how processing factors affect the physicochemical and nutritional qualities of porridge and congee, and how to fortify and replace functional components in instant porridge and congee. Nowadays, consumers are expressing an increase in desire for food products that are more nutritious, accessible, and natural without compromising on health objectives, flavors, or ingredients. Most significantly, these food products must aid consumers in keeping up with their hectic schedules. Porridge, or congee, is well-known for being a nutritious dish that is simple to prepare, easy to digest, and great for feeding the sick and toothless, such as infants and the elderly. In spite of that, porridge, or congee, is a starchy food with a low nutritional content. The use of different kinds of beans, grains, and vegetables as functional ingredients could provide higher nutritional values as compared to plain porridge or congee. Thus, food researchers take the initiative in developing instant fortified porridge and congee to fulfil consumers’ demand for a healthy and convenient food. Previous studies have proven that instant fortified porridge and congee have significantly improved the nutritional content of plain porridge and congee. Overall, this review provides valuable insights into the potential contribution of rice congee to the dietary needs of consumers (especially the elderly), shedding light on its significance as a functional food option.